A Brief Analysis on Vocabulary Learning Strategies in Second Language - Temmy, Temmy (Humaniora, 2013)
This article tries to explore the usage of vocabulary learning strategies in second language learning on students with different background. It attempts to elicit useful ideas and gives a practical guidance in learning Chinese as a second language. This work explains how learning environment, cultural background and proficiency level can highly affect the choice of learning strategies. And even though students are learning different languages, there are similarities in their choice of strategies during the process of acquiring the target language.